2022
DOI: 10.1039/d1fo03396d
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation effects of grape seed proanthocyanidin extract on inflammation and oxidative stress in a d-galactose-induced aging mouse model by modulating the gut microbiota

Abstract: Grape seed proanthocyanidin extract delayed the d-galactose-induced aging process in mice through the gut microbiota–liver axis and microbiota–brain axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…A previous study found that the abundance of Lachnospiraceae_NK4A136_group can improve the intestinal barrier function of aging rats. This group comprises one of the main butyrate-producing bacteria, and its abundance is significantly negatively correlated with the level of inflammation [ 49 , 50 ]. In addition, Eubacterium species, such as E. rectale and E. eligens , have been positively associated with several markers of lower frailty, improved cognitive ability, and increased production of SCFA and branched-chain fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the abundance of Lachnospiraceae_NK4A136_group can improve the intestinal barrier function of aging rats. This group comprises one of the main butyrate-producing bacteria, and its abundance is significantly negatively correlated with the level of inflammation [ 49 , 50 ]. In addition, Eubacterium species, such as E. rectale and E. eligens , have been positively associated with several markers of lower frailty, improved cognitive ability, and increased production of SCFA and branched-chain fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Generally, the ratio of F/B is an indicator of the health of intestinal microbiota. 43 Studies have suggested that d -gal intervention led to a reduction in Firmicutes and the ratio of F/B at the phylum level, 44 which matched our findings. After the intervention of RLWPF and VLRLF, the ratio of F/B was raised, indicating that the RLWPF and VLRLF may reverse the imbalance of gut microbiota by regulating the ratio of F/B at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperoxaluric rats exhibited a deficiency in GSH content, which was related to the reduction in GSH-synthesizing enzyme activities, glutathione reductase, and glucose 6-phosphate dehydrogenase. 18, 60 On the other hand, GSE exhibited remarkable antioxidant activity in different non-renal models, for instance, type-1 diabetes, 61 titanium dioxide nanoparticle-induced hepatotoxicity, 28 and D-galactose-induced ageing mouse model, 62 and in diverse renal models including renal ischemia-reperfusion, 53 carboplatin and thalidomide, 34 cisplatin, 30 and induced renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, GSE showed an anti-inflammatory effect in many other models, including the monocrotaline-induced pulmonary arterial hypertension 66 and D-galactose-induced ageing. 62 As for renal action, GSE demonstrated reno-protective activity via attenuating inflammation in diverse renal models, including renal ischemia/reperfusion, 53 arsenic, 55 carboplatin, and thalidomide-induced renal injury 34 and renal fibrosis. 67 Based on the present results and previous literature, it could be suggested that GSE produces anti-inflammatory actions by affecting the canonical pathway of NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%